ANALISIS FAKTOR INTERNAL DAN FAKTOR EKSTERNAL TERHADAP NILAI PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Hilmi, Roni Yul; Tipa, Handra (SCIENTIA JOURNAL, 2021)
The value of the company is the value owned by the company in line with the value of the shares traded in the capital market. The purpose of this study was to test the Current Ratio (CR), Return on Assets (ROA), Debt to Asset Ratio (DAR) and Inflation to Firm Value. The population in this study are manufacturing companies in the metal sub-sector and the like which are listed on the Indonesia Stock Exchange. The sample selection used purposive sampling method which resulted in a sample of 8 companies. The data analysis method in this study is the classical assumption test using normality test, multicollinearity test, heteroscedasticity test and autocorrelation test, multiple linear regression analysis test and hypothesis testing using t test, f test and coefficient of determination test. The data analysis test method in this study proves that the Current Ratio (CR) and Return on Assets (ROA) variables partially affect the Firm Value (PBV), and vice versa the Debt to Asset Ratio (DAR) and Inflation variables partially have no effect on the Value company (PBV). The variables of Current Ratio (CR), Return on Assets (ROA), Debt to Asset Ratio (DAR) and Inflation simultaneously affect firm value.